Alcohol Screening and Brief Advice in NHS General Dental Practices: A Cluster Randomized Controlled Feasibility Trial. (18th March 2019) - Ntouva, Antiopi; Porter, Jessie; Crawford, Mike J; Britton, Annie; Gratus, Christine; Newton, Tim; Tsakos, Georgios; Heilmann, Anja; Pikhart, Hynek; Watt, Richard G
Abstract : The results of this study have demonstrated the feasibility and acceptability of NHS dentists screening for alcohol misuse and delivering brief advice to eligible patients attending general dental practices. Recruitment, retention and delivery targets were all met and the process evaluation demonstrated the intervention and study procedures were acceptable. Abstract: Aim: To assess the feasibility and acceptability of screening for alcohol misuse and delivering brief advice to eligible patients attending NHS dental practices in London. Methods: A two-arm cluster randomized controlled feasibility trial was conducted. Twelve dental practices were recruited and randomized to intervention and control arms. Participants attending for a dental check were recruited into the study and were eligible if they consumed alcohol above recommended levels assessed by the AUDIT-C screening tool. All eligible participants were asked to complete a baseline socio-demographic questionnaire. Six months after the completion of baseline measures, participants were contacted via telephone by a researcher masked to their allocation status. The full AUDIT tool was then administered. Alcohol consumption in the last 90 days was also assessed using the Form 90. A process evaluation assessed the acceptability of the intervention. Results: Over a 7-month period, 229 participants were recruited (95.4% recruitment rate) and at the 6 months follow-up, 176 participants were assessed (76.9% retention rate). At the follow-up, participants in the intervention arm were significantly more likely to report a longer abstinence period (3.2 vs. 2.3 weeks respectively, P = 0.04) and non-significant differences in AUDIT (44.9% vs. 59.8% AUDIT positive respectively, P = 0.053) and AUDIT C difference between baseline and follow-up (−0.67 units vs. −0.29 units respectively, P = 0.058). Results from the process evaluation indicated that the intervention and study procedures were acceptable to dentists and patients. Conclusions: This study has demonstrated the feasibility and acceptability of dentists screening for alcohol misuse and providing brief advice.